2022
DOI: 10.26480/itechmag.04.2022.01.09
|View full text |Cite
|
Sign up to set email alerts
|

Study on Research Works and Future Research Directions of Post-Graduate Program at Pathology Department, Iaas, Rampur, Chitwan, Nepal

Abstract: The Institute of Agriculture and Animal Science (IAAS) under Tribhuwan University (TU) has been carrying out various disciplinary and system research works through post-graduate students' research and publishing their findings through the M.Sc.Ag and Ph.D. thesis dissertations. Various thesis written by researchers under IAAS were collected and the appraisal of pathological research works on major cereals, vegetable crops, legume crops, oilseed crops and high-value crops along with ideas on management practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…PWL% was found lowest (10.76%) in fruits coated with aloe Vera gel under CoolBot storage at 35 days of storage. This finding coincides with the report of Bhusal (2002), Bastakoti, and Gautam (2007) in Mandarin fruit. They concluded that aloe Vera gel coated fruits act as a wax on a fruit that might have been an effective treatment to reduce weight loss by checking the stomata and lenticels of the cell wall of the fruits which reduces the rate of respiration and transpiration.…”
Section: Cumulative Physiological Weight Loss Percentage At 35 Days O...supporting
confidence: 93%
“…PWL% was found lowest (10.76%) in fruits coated with aloe Vera gel under CoolBot storage at 35 days of storage. This finding coincides with the report of Bhusal (2002), Bastakoti, and Gautam (2007) in Mandarin fruit. They concluded that aloe Vera gel coated fruits act as a wax on a fruit that might have been an effective treatment to reduce weight loss by checking the stomata and lenticels of the cell wall of the fruits which reduces the rate of respiration and transpiration.…”
Section: Cumulative Physiological Weight Loss Percentage At 35 Days O...supporting
confidence: 93%